(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
In today’s competitive job market, career skills are essential for success. However, students’ uncertainty over their capabilities to enter the job market raises concern as to how they are prepared for employment. This study examines the level of development of the respondents in the different career skills to formulate interventions to better prepare students for the demands of the modern workforce. This quantitative study utilized descriptive comparative design to describe the respondents’ level of development and its comparison when the respondents are grouped based on their profile. The researchers randomly chose 203 Grade 11 and 12 students. Weighted mean and standard deviation was used to present the level of development, while ANOVA and t-test was used to determine significant differences. Results revealed that the respondents are highly developed with numeracy skills being the highest rated area. While other areas also exhibit high development, it is not considered optimal and thus there is room for improvement. Significant differences in their development was also found along sex, GPA, and highest educational attainment wherein females, students with higher GPA, and parents with higher educational attainment were more developed. These findings highlight the importance of considering demographic factors in understanding students’ readiness for the workforce. There is a need to further improve the development of career skills among the respondents. Future research and interventions should take into account these factors to enhance students’ career preparedness.